سيمياء القصيدة الحزن علامة شعرية دالة - القصيري، فيصل صالح (دار الأطروحة للنشر العلمي, 2018)
السيمياء مفهوم واسع وشامل ومتعدد ومتطور بحيث يؤلف عالما قائما بذاته، ويشتغل عالم السيمياء -بمنظوماته النظريّة والاصطلاحيّة والمفهوميّة – بالدرجة الأولى على عنصر اللغة وخصوصيتها التعبيريّة وحمولتها الدلاليّة، وحين يدخل فضاء القصيدة يتحوّل إلى حامل علامي ثريّ يغني القصيدة ويسهم في تطوير بنيتها ورؤيتها معاً. وتعدّ علامة الحزن إحدى أهمّ العلامات السيميائية في الشعرية العربية القديمة والحديثة. الشاعر محمد مردان أحد أبرز الشعراء المعاصرين الذين تفاعلوا شعريا مع موضوع الحزن بوصفها دالاً سيميائيا أصيلا، إذ استطاع أن يوظف طاقة الحزن توظيفياً شعرياً لافتاً لعين القراءة على مستوى الصورة واللغة والفاعلية الشعرية العامة والخاصة، من خلال تجربة ثرة لها حزنها الخاص الذي يتوفر على نكهة خاصة ومزاج خاص ووعي نوعي خاص، وغالباً ما ارتبطت علامة الحزن عنده بمشروع الحب الذي هيمن هيمنة تكاد تكون مطلقة على شعرية دواوينه كلها، وثمة علاقة وطيدة بين الحب والحزن في الجوهر العميق للعلامة الشعرية التي يسعى الشاعر محمد مردان على نحو خاص إلى إنتاجها. أما الشاعر عيسى الشيخ حسن يحول الحزن المتشظي في أعماقه، وفي واقعه، إلى حالة شعرية خاصة عبر لغة منزاحة تتسم مفرداتها بالأناقة، وتراكيبها بغنى المعطيات الجمالية والدلالية والإيقاعية. ولعل عناية الشاعر بلغته تعبر عن وعيه بأهمية السياق اللغوي في أنتاج شعرية التجربة، وذلك لما يمثله هذا السياق في عملية الخلق الإبداعي، فهو مصدر الرئيس لاستمرار البث الشعري. وإذا كانت اللغة تستجيب لرؤى وهواجس ومكابدات الشاعر، فتنقلها من مكامنها المستترة إلى فضاء الكتابة والرحب، فإنها تستجيب على نحو أفضل لتجربة الحزن بصفها تجربة نفسية –وجدانية ذات بعد أنساني، وتمثل على نحو ما فلسفة حياة بطريقة شعرية.
Semantics is an immense and comprehensive concept with its multiple and developed functions. It constitutes a world of its own. The semantologist is working with his theoretical and conceptual systems, and he is primarily concerned with the element of language, its expressive specificity and its semantic load, and when this element enters the space of the poem, it becomes a rich material carrier that enriches the poem and contributes to the development of its structure and vision together. The sign of sadness is one of the most important signs of semiotics in ancient and modern Arabic poetics. The poet, Mohammad Mardan, is one of the most prominent modern poets who have interacted poetically with the theme of grief as an authentic signifier. as he was able to employ the energy of grief by employing poetry, pointing to the eye of reading at the level of image, language, specific and general poetic effectiveness, through a rich experienceand a special temperament and special awareness. His sadness was often associated with the love project, which absolutely dominated almost the poetics of all his writings. There is a strong relationship between love and sorrow in the deep essence of the poetic sign that poet Mohammed Mardan seeks in particular to produce. The poet Issa Sheikh Hassan transforms the splintering sadness in his depths and reality, into a specific poetic state, especially through the language of displacement which is characterized by its elegance, and its structures rich in aesthetic, semantic and rhythmic data. Perhaps the attention of the poet in his language expresses his awareness of the importance of the linguistic context in the production of the poetics of experience, because of the representation of this context in the process of creative creation, it is the major source for the transmission of poetry. If the language responds to the poet's perceptions, concerns and preoccupations, then moves them from hidden sources to the extensive space of writing, they respond better to the experience of grief as a psychological- emotional experience with a human dimension. It resembles somehow a poetic philosophy of life.
Keywords: الشعر العربي -- الشعراء العرب -- نقد الشعر -- الدواوين والقصائد -- علم السيميائيات -- مستخلصات الأبحاث -- العلامات الشعرية -- العلامات السيميائية